Regulation of plant immunity via small RNA-mediated control of NLR expression - López-Márquez, Diego; Del Espino Pérez, Ángel; Ruiz-Albert, Francisco Javier; Rodríguez-Bejarano, Eduardo; Brodersen, Peter; Beuzón-López, Carmen del Rosario (Oxford University Press, 2023)
Plants use different receptors to detect potential pathogens: membrane-anchored pattern recognition receptors (PRRs) activated upon perception of pathogen-associated molecular patterns (PAMPs) that elicit pattern-triggered immunity (PTI); and intracellular nucleotide-binding leucine-rich repeat proteins (NLRs) activated by detection of pathogen-derived effectors, activating effector-triggered immunity (ETI). The interconnections between PTI and ETI responses have been increasingly reported. Elevated NLR levels may cause autoimmunity, with symptoms ranging from fitness cost to developmental arrest, sometimes combined with run-away cell death, making accurate control of NLR dosage key for plant survival. Small RNA-mediated gene regulation has emerged as a major mechanism of control of NLR dosage. Twenty-two nucleotide miRNAs with the unique ability to trigger secondary siRNA production from target transcripts are particularly prevalent in NLR regulation. They enhance repression of the primary NLR target, but also bring about repression of NLRs only complementary to secondary siRNAs. We summarize current knowledge on miRNAs and siRNAs in the regulation of NLR expression with an emphasis on 22 nt miRNAs and propose that miRNA and siRNA regulation of NLR levels provides additional links between PTI and NLR defense pathways to increase plant responsiveness against a broad spectrum of pathogens and control an efficient deployment of defenses
Keywords: Plantas - Resistencia a plagas y enfermedades; Effector-triggered immunity; miRNA; NLR proteins; Plant immunity; Post-transcriptional gene silencing; R genes; RNAi; Secondary siRNA